Metal 3D printing: Patent law, trade secrets, and additive manufacturing - Rimmer, Matthew (Frontiers in Research Metrics and Analytics, 2022)
There has been significant investment in research and development in respect of metal 3D printing in the United States (as well as a number of other jurisdictions). There has been growing conflict over the ownership of intellectual property in respect of metal 3D printing (involving not only patents but also trade secrets and confidential information, as well as contract law and unfair competition). In 2018, Desktop Metal Inc. launched litigation against Markforged Inc. and Matiu Parangi in relation to intellectual property and metal 3D printing in the United States. As well as complaints of patent infringement, Desktop Metal Inc. has alleged that the defendants had engaged in acts of trade secret misappropriation, unfair and deceptive business practices, and breach of contract. Markforged Inc. made various counter-claims of its own. In July 2018, a Federal Jury found that Markforged Inc. did not infringe two patents held by its rival Desktop Metal Inc. Claims of further violations of trade secrets and contract law were also considered. In the end, the dispute was settled, with neither party obtaining an advantage in the litigation. There was further conflict over whether the terms of the settlement in respect of non-disparagement were honoured. The parties have also faced further intellectual property conflict. In 2021, Continuous Composites has filed a patent infringement lawsuit against Markforged Inc. In 2021, Desktop Metal Inc. brought legal action against SprintRay in Germany. Drawing upon this case study, this paper considers whether metal 3D printing will disrupt patent law, policy, and practice. It also explores the tension between the use of trade secrets in commercial 3D printing (such as in metal 3D Printing), and the open source ethos of the Maker Movement. This paper considers the larger implications of this intellectual property dispute over metal 3D printing for scarcity, regulation, and the abundance society. It also explores the innovation policies of the Biden administration in respect of advanced manufacturing – with a focus upon metal 3D printing and additive manufacturing.